Determinants of Judicial Efficiency in Morocco (Global Journal of Management and Business Research, 2021)
In this paper, we aim to measure Moroccan judicial efficiency and identify its determinants during the implementation of judicial reform. For this, we use a two-stage approach. First, we use data envelopment analysis (DEA) under output orientation to measure the efficiency of the 109 Moroccan courts. In the second stage, we explore determinants of efficiency using the Ordinary Least Squares regression model. The results show a low level of courts efficiency of 56.2% in 2018, despite an improvement during the reform implementation period. At the same time, the results show that efficiency increases in populated cities with high demands on justice, and in courts with high proportions of cases in process, and employing senior judges. Therefore, this paper presents some managerial implications for court managers and provides further research directions for assessing judicial efficiency
Keywords: data envelopment analysis; efficiency measurement; judicial efficiency; efficiency determinants; moroccan courts; judicial reform